(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
Data about floristic records of Rudbeckia triloba L . Asteraceae a new alien species in Ukrainian flora wer e reported. The main centers of species i ntroduction in Ukraine are Donetsk Botanical Garden of NAS of Ukraine (cultivated since 1982), M.M. Hryshko National Botanical Garden of NAS of Ukraine (since 1983), Botanical Garden of I.I. Mechnikov Odesa National University and also numerous private gar dens (е .g. Uzhhorod, Transcarpathia Reg ion since 1973 , Kryvyi Rig of Dnipropetrovsk Reg ion 2013, and Zhytomyr Reg ion 2016 ). As escaped plants they were recorded in several localitets : Kharkiv (2010), vicinity of vill age Dachne of Bakhchysaray Distr ict , and Simferopol’ ( vill age Zarichne of Simferopol’ Distr ict , AR Crimea ( 2018), Lozova, Kharkiv Reg ion ( 2014), Chernivtsi (2014), Odesa (2014) 2014), Cherniakhiv (2015), Malyn (2017), vill age Ivnytsia of Andrushivskyi Distr ict , Zhytomyr Reg ion ( 2019), Rachiv (2 016), between Perechyn and vill age Malyi Bereznyi of Velykyi Bereznyi Distr ict , Transcarpathia Reg ion ( T axonomical and morphological characteristics, chorological data ecological and coenotic peculiarities we re given. The species has North American origin I t is ergasioph igoph yte or colonophyte according to degree of naturalization Mainly, plants gr e w in unformed plant communities I n Zhytomyr Polissia the species was fixed in the composition of u nion Arrhenatherion elatioris Luquet 1926 (o rdo Arr henatheretalia elatioris Tx . 1931, c lass Molinio Arrhenatheretea Tx . 1937 in xero mesophytic conditions under the full light and u nion Aegopodion podagrariae Tx . 1967 (o rdo Circaeo lutetianae Stachyetalia sylvaticae Passarge 1967, c lass Epilobietea angust ifolii Tx . et Preising ex von Rochow 1951 in mesophytic conditions under significant shading. The map of distribution of the species in Ukraine was presented.